Energy efficient techniques of wireless network - Yeo, Chuen Hwee. (2012)
Wireless sensor network consists of hundreds to thousands of sensor nodes deployed in an area of interest to gather information. The sensor nodes are harshly energy constrained and it is necessary to organize in a way to save the energy during processing, receiving and communication with a base station. Sensor nodes are clustered into different clusters.